The Relationship between Health Education Interventions and Changes in Parental Knowledge and Attitudes in Overcoming Stunting in Early Childhood - Melia Eka Daryati; Muhammad Hatta; Wembrayarli Wembrayarli (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
Stunting in early childhood is a global concern because of its long-term impact on children's growth and development. This study aims to evaluate the relationship between health education interventions and changes in parental knowledge and attitudes in dealing with stunting in early childhood. The research method used is an intervention study with a quasi-experimental design. The sample for this study consisted of parents of early childhood children who were selected using convenience sampling. The health education intervention was carried out through workshops, providing materials, and discussion sessions for two months. Data collection was carried out before the intervention (baseline) and after the intervention using a questionnaire to measure the level of knowledge and attitudes of parents towards stunting. Data analysis was carried out using the paired t-test and Pearson correlation. The results of the study showed a significant increase in parental knowledge and attitudes after the health education intervention with a value of p = 0.001. In addition, there was a significant positive relationship between increased knowledge and changes in parental attitudes in overcoming stunting in early childhood (r = 0.75, p < 0.01). In conclusion, health education interventions are effective in increasing parental knowledge and attitudes and can potentially reduce stunting rates in early childhood.